Development of Google Site-Based Interactive Media to Increase Student Activeness in Pancasila Education Learning - Isra Septia Ningsih; Mislan Mislan; Heroza Firdaus (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The purpose of this research is to create interactive media based on Google Sites and to determine how well it can improve student participation in Pancasila education. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 20 fifth-grade students of SDN 87/VII Limbur Tembesi II. Data collection was conducted through observation, questionnaires, interviews, and documentation. A quantitative and qualitative descriptive approach was used to analyze the data. The results of the study indicate that the developed media has a very valid feasibility level based on assessments by language experts (95%), material experts (100%), and media experts (87.5%). Moreover, it has been proven that Google Sites-based interactive media successfully improve student participation from the less good category to very good. Therefore, this media can be used as a learning alternative that can increase student engagement.